1. The problem statement, all variables and given/known data F(s)=(−2s−2)/((s−1)2+9) Find f(x) by computing L-1[F(s)] = f(x). 2. Relevant equations 3. The attempt at a solution I made put (s-1) in place of s in the numerator, then compensated for that by subtracting 2: F(s) = (-2(s-1) - 2 -2 ) / ((s-1)2 + 9) Then s-1 becomes s... F(s) = (-2s - 4) / (s2 + 32) Split this into 2 parts: -2s / s2 + 32 and (-4/3)(3 / s2 + 32) This gives -2cos(3x) - (4/3)sin(3x) as f(x). But it's wrong... what should I have done differently?